Setor sucroenergético: dinâmica produtiva do açúcar no Brasil - Lima, Andreza Tuckmantel de (Universidade Federal de São Carlos, 2020)
Brazil stands out worldwide in the sugar-energy sector, in world rankings it presents itself as the largest producer and exporter of sugar and the second largest producer of ethanol. In this sense, it is important to better understand the productive dynamics of sugar and its economic variables (domestic and international prices) to contribute positively to the strengthening of public policies and actions of the private sector. Thus, the general objective of this work is to analyze the productive and economic dynamics of Brazilian sugar between the 2003/2004 and 2019/2020 harvests, through selected economic variables and the calculation of correlation index. Specifically, to identify periods of variations in sugar production, followed by a qualitative analysis of these periods, as well as to verify the correlations between sugar production and product prices in the domestic and international markets. This research has an exploratory character, with the use of secondary data, obtained through bibliographic reviews, encompassing books, academic papers, websites of public and private institutions, etc. Pearson's Correlation Index was used to calculate the correlation between the sugar production variable and the variables of domestic and international prices. As results, positive correlations were found between: sugar production and product prices in the domestic and international markets; domestic and international sugar prices. Six periods with variations in sugar production were also identified and their respective qualitative and quantitative analyses were made. Moreover, as expected, it could be inferred that Brazil does not dictate the price of sugar in the foreign market, but has an active participation in it, much due to being the largest producer and exporter of this commodity. It was possible to conclude that the production mix of sugarcane depends on complex analyses and several factors, many of them including at global levels. However, the destination of sugar to the international market is historically consolidated and this was found during the period analyzed. Finally, it is concluded that the productive dynamics of sugar is important for the decision-making of the private sector, guideing the right amount and time to sell sugar in the domestic and/or international market.
Sugar-energy sector: sugar production dynamics in Brazil
Keywords: Açúcar; Sucroenergético; Índice de preços; Correlação; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS